Lactiplantibacillus plantarum 22 A-3 ameliorates leaky gut in mice through its anti-inflammatory effects - Takashi Kobayashi; Takaomi Kessoku; Michihiro Iwaki; Asako Nogami; Masato Yoneda; Satoru Saito; Yoshie Yamana; Yosuke Nishitani; Hiroshige Kuwahara; Atsushi Nakajima (Scientific Reports)
Abstract There are limited studies on the improvement of leaky gut with minor inflammation associated with various diseases. To explore the therapeutic potential of Lactiplantibacillus plantarum 22 A-3, a member of the Lactobacillus species, in addressing a leaky gut. Lactiplantibacillus plantarum 22 A-3 was administered to a leaky gut mice model with low dextran sulfate sodium concentrations. The Lactiplantibacillus plantarum 22 A-3-treated group exhibited amelioration of increased intestinal permeability, as indicated by lower blood fluorescein isothiocyanate-dextran levels compared with that of the control group. Furthermore, the messenger RNA expression of interleukin-10, an anti-inflammatory cytokine, was upregulated in the small intestine of Lactiplantibacillus plantarum 22 A-3-treated mice. Moreover, forkhead box P3 was upregulated in the small intestine and colon following Lactiplantibacillus plantarum 22 A-3 administration. Flow cytometry showed that forkhead box P3-positive regulatory T cells tended to increase in the small intestine and colon; however, this was not significant. Messenger RNA levels for the pro-inflammatory cytokines, interleukin-1 beta, and tumor necrosis factor-alpha showed no significant changes in the small intestine; however, their expressions significantly decreased in the colon. Blood fluorescein isothiocyanate-dextran levels showed that intestinal permeability also decreased in Lactiplantibacillus plantarum 22 A-3-dead bacteria. The bacterial component of Lactiplantibacillus plantarum 22 A-3 ameliorates increased intestinal permeability through its anti-inflammatory effect in the intestinal tract and may be a novel treatment for leaky gut.